A influência dos fatores socioeconômicos na sobrevida global dos pacientes submetidos ao transplante de células tronco hematopoéticas - Candelaria, Ana Claudina Conduta [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The Hematopoietic Stem Cell Transplantation (HSCT) is one of the therapeutic approaches in the treatment of diseased bone marrow. HSCT causes social, psychological and family problems to the patients. The Amaral Carvalho Foundation, Jahu, through the Bone Marrow Transplantation Service who started its activities in 1996, has been firming the commitment to patients from all Brazil regions, working in a team and providing humane treatment to the patients. The Social Service, integral part of this team, over the years developed actions aiming to minimize the difficulties encountered by patients during the long period of treatment. During the proposed period of this study (1996-2012), were analyzed 997 medical records. The objectives were: 1) Evaluate the overall survival of onco-hematological patients who underwent to Hematopoietic Stem Cell Transplantation of Amaral Carvalho Foundation. 2) Describe the general characteristics of the patients of Hematopoietic Stem Cells Transplantation service of Amaral Carvalho Foundation. 3) Characterize the socio-economic status of the studied population. 4) Identify the variables associated with overall patient survival. 5) Determine the behavior of the variables of interest against socio economic classification of the studied population. Clinical research was performed, conducted through an exploratory delimitation, where were investigated existing associations between variables, socio-economic classification and overall survival, the socio-economic classification was realized by the social service through a form developed according to techniques already consolidated in Brazil. In the overall survival analysis the result founded was 46%, when analyzed the socio- economic classification the patients were divided in 4 groups, social class A - 49 (5%) patients, social class B - 197 (20%) patients, social class C - 352 (35,3%) patients, social class D - 207 (20,7%) patients and social ...

O Transplante de Células Tronco Hematopoéticas (TCTH) é uma das abordagens terapêuticas para correção da medula óssea doente. TCTH causa aos pacientes problemas de ordens sociais, psicológicas e familiar. O Hospital Amaral Carvalho de Jahu, através do Serviço de Transplante de Medula Óssea com início das atividades em 1996, vem firmando o compromisso com os pacientes de todas as regiões do Brasil, trabalhando em equipe e oferecendo tratamento humanizado aos pacientes. O Serviço Social, parte integrante desta equipe, ao longo dos anos desenvolveu ações voltadas para minimizar as dificuldades encontradas pelos pacientes durante o longo período de tratamento. Durante no período proposto para este estudo, foram analisados 997 prontuários. Os objetivos foram: 1) Avaliar a sobrevida global dos pacientes onco-hematológicos que realizaram Transplante de Células Tronco Hematopoéticas da Fundação Hospital Amaral Carvalho. 2) Descrever as características gerais dos pacientes do serviço de Transplante de Células Tronco Hematopoéticas da Fundação Hospital Amaral Carvalho. 3) Caracterizar o nível socioeconômico da população estudada. 4) Identificar as variáveis associadas à sobrevida global do paciente. 5) Determinar o comportamento das variáveis de interesse frente a classificação socioeconômica da população estudada. Foi realizada pesquisa clinica, conduzida mediante um delineamento exploratório, onde foram investigadas associações existentes entre as variáveis, classificação socioeconômica e sobrevida global, a classificação socioeconômica foi realizada pelo serviço social através de formulário desenvolvido de acordo com técnicas já consolidadas no Brasil. Na análise da sobrevida global dos pacientes o resultado encontrado foi de 46%, quando analisada a classificação socioeconômica os pacientes foram divididos em 4 grupos, classe social A – 49 (5%) pacientes, classe social B – 197 (20%) ...
Keywords: Transplante de células-Tronco; Serviço social de casos; Pacientes - Aspectos sociais; Pacientes - Aspectos econômicos; Qualidade de vida; Stem cell Transplantation